The environmental psychology of prisons and jails : creating humane spaces in secure settings - Wener, Richard (Cambridge series in environment and behavior., 2012)
This book distills thirty years of research on the impacts of jail and prison environments. The research program began with evaluations of new jails that were created by the US Bureau of Prisons, which had a novel design intended to provide a non-traditional and safe environment for pre-trial inmates and documented the stunning success of these jails in reducing tension and violence. This book uses assessments of this new model as a basis for considering the nature of environment and behavior in correctional settings, and more broadly in all human settings. It provides a critical review of research on jail environments and of specific issues critical to the way they are experienced and places them in historical and theoretical context. It presents a contextual model for the way environment influences the chance of violence.